Influence of Obesity in Atherosclerosis in the etiology and pathogenesis of periodontal diseases - Norma Mur Villar; Carla María García San Juan; Maricel Castellanos González; Nora Sexto Delgado; Carlos Moisés Méndez Castellanos; Wendy Gamio Pruna (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Obesity is a chronic multifactor disease, considered a nutritional disorder which seems to have an ascending character in parts of the world and mainly in America. Recent studies show a linking between obesity and atherosclerosis with periodontopathies. With the objective of describing the relationship between obesity and atherosclerosis with the development of periodontal diseases an updated bibliography review was carried out. Articles were identified through an automated search in data bases SCOPUS and GOOGLE. Twenty two original articles were selected. It was concluded that in obesity so as in atherosclerosis pro-inflammatory substances are discharged which play an important role in the ethiopathogenesis of periodontal disease.